SPECIFIC FEATURES OF TEACHING THE RUSSIAN LANGUAGE IN HIGHER EDUCATIONAL INSTITUTIONS (International journal of artificial intelligence, 2026)
This article examines the specific pedagogical and methodological aspects of teaching the Russian language in higher educational institutions of Uzbekistan, in particular, on the example of the Academy of the Ministry of Internal Affairs. The author justifies the importance of comparative-typological analysis in teaching the Russian language and shows ways to overcome obstacles to understanding a literary text among Uzbek-speaking students. The article analyzes the effectiveness of using heuristic methods (problematic research) and search dialogues in developing speech through literary texts. It also covers the issues of expanding students' aesthetic outlook by finding commonalities between Russian and Uzbek literature.